2011
DOI: 10.2146/ajhp100410
|View full text |Cite
|
Sign up to set email alerts
|

Determining vancomycin clearance in an overweight and obese population

Abstract: Use of ABW proved to be superior compared with total body weight when estimating vancomycin clearance in overweight and obese patients. While there was no difference in bias between methods, the modified Leonard and Boro method was significantly more precise than the Rushing and Ambrose method in predicting SVCs when dosing vancomycin for obese patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…We present one of the largest cohorts published to date evaluating vancomycin, obesity, and nephrotoxicity [13][14][15][16][17][18][19][29][30][31]. Our study observed a 21% incidence of nephrotoxicity (obese = 18% vs. lean = 23%) among infectious episodes treated with vancomycin and a 12% incidence of new-onset hemodialysis (obese = 10% vs. lean = 14%).…”
Section: Discussionmentioning
confidence: 78%
“…We present one of the largest cohorts published to date evaluating vancomycin, obesity, and nephrotoxicity [13][14][15][16][17][18][19][29][30][31]. Our study observed a 21% incidence of nephrotoxicity (obese = 18% vs. lean = 23%) among infectious episodes treated with vancomycin and a 12% incidence of new-onset hemodialysis (obese = 10% vs. lean = 14%).…”
Section: Discussionmentioning
confidence: 78%
“…Richardson et al [20] reported that increasing BMI categories were associated with a C min >20 μg/mL. Leong et al [21] demonstrated that an adjusted body weight was more accurate at predicting vancomycin clearance in obese individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identified greater CLvanc in obese patients with normal serum creatinine [ 8 , 9 , 15 ]. As obese patients have a larger volume of distribution (Vd), they may have a higher CrCL and CLvanc.…”
Section: Discussionmentioning
confidence: 99%